Imaging Molecular Recognition by the Inhibitory Human Natural Killer Cell Receptor KIR2DL1 - Pageon, Sophie Victoria (Imperial College London, 2012)
Natural Killer (NK) cells are lymphocytes that identify and kill virus-infected and tumour cells dependent on recognition via numerous activating and inhibitory surface receptors. The mechanisms by which NK cells can integrate activating and inhibitory signals at the immune synapse remain unclear, although a correlation has been established between a cell’s response and the organisation of receptors into specific molecular patterns at the synapse. Here, I used three novel imaging techniques to investigate the spatial and temporal dynamics of molecular recognition by human NK cells. The inhibitory NK cell receptor KIR2DL1 was tagged with the photoswitchable protein tdEosFP, which can be irreversibly switched from a green to red fluorescent state using ultraviolet light. First, tdEosFP was used to visualise the localisation and organisation of KIR2DL1 at the synapse at unprecedented resolution using photoactivated localisation microscopy. KIR2DL1 was organised in pre-existing protein clusters with a diameter of 84.2 ± 5.4 nm. Upon receptor ligation, clusters became smaller by 15% and denser by 27%, in an actin-independent manner. Surprisingly, the ligation of other receptors such as NKG2D and CD94/NKG2A affected the nanoscale organisation of KIR2DL1 by increasing the cluster density by 18-19% and decreasing the average cluster diameter by 20%. Thus, the distribution of KIR2DL1 is directly influenced by other receptors. Second, the movement of photoswitched molecules was temporally and spatially resolved and the diffusion coefficient of KIR2DL1 in the membrane of NK cells determined to be 0.167 ± 0.077 μm2.s-1. KIR2DL1 was continuously recruited to an immune synapse, where it remained stable, unless a second synapse was formed, in which case KIR2DL1 was able to traffic between synapses. Finally, a system using a photocleavable peptide to temporally control NK cell inhibition was established. This enables the timing of inhibitory signalling mediated by KIR2DL1 to be controlled. Together, these complementary approaches provide important new insights on how the nanoscale organisation of KIR2DL1 at the synapse can reflect different stimulatory conditions and novel spatio-temporal information on KIR2DL1 recruitment to the synapse.